Improving the Performance of Yonzipur 11/DW Soldiers in View of Leadership Style, Work Discipline and Motivation - Agus Iskarman; Asep Kurniawan (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2024)
The Yonzipur 11 Durdhaga Wighra combat assistance unit is responsible for the construction of military infrastructure on the battlefield and in peacetime. However, despite the cessation of hostilities, there is a possibility that some soldiers may still engage in misconduct and lack motivation, which could negatively impact their performance. This research aims to enhance performance by examining the influence of leadership style, work discipline, and motivation. The research method employed quantitative methods with descriptive analysis. The research sample consisted of 84 respondents, selected through random sampling. The results of the descriptive analysis of leadership style, work discipline, motivation, and performance of soldiers were categorized as sufficient. The results of data analysis indicated a significant positive effect of leadership style and work discipline on the performance of soldiers through direct and indirect motivation. However, work discipline exhibited a negative effect on the performance of soldiers. The role of motivation in positively mediating the influence of leadership style and work discipline on the performance of soldiers demonstrates the importance of motivation as an organizational priority, as it provides insight into the performance of soldiers.